2020
DOI: 10.1002/pros.24027
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CPT1B as a potential therapeutic strategy in castration‐resistant and enzalutamide‐resistant prostate cancer

Abstract: BackgroundProstate cancer is characterized by aberrant lipid metabolism, including elevated fatty acid oxidation. Carnitine palmitoyltransferase 1B (CPT1B) catalyzes the rate‐limiting step of fatty acid oxidation. This study aimed to determine if CPT1B has a critical role in prostate cancer progression and to identify its regulatory mechanism.MethodsCPT1B expression data from The Cancer Genome Atlas and Gene Expression Omnibus databases was compared with patient survival data. A tissue microarray was construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…27 Although the mechanism of androgen resistance is not fully clear, abnormal fatty acid metabolism has been shown to promote the resistance of CRPC cells to enzalutamide. 28 Overexpression of carnitine palmitoyltransferase 1B (CPT1B), a rate-limiting step of fatty acid oxidation, is reported to significantly increase enzalutamide resistance via increasing AKT expression and phosphorylation in CRPC cells. 28 This indicates that enhanced fatty acid oxidation could promote the drug resistance of CRPC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Although the mechanism of androgen resistance is not fully clear, abnormal fatty acid metabolism has been shown to promote the resistance of CRPC cells to enzalutamide. 28 Overexpression of carnitine palmitoyltransferase 1B (CPT1B), a rate-limiting step of fatty acid oxidation, is reported to significantly increase enzalutamide resistance via increasing AKT expression and phosphorylation in CRPC cells. 28 This indicates that enhanced fatty acid oxidation could promote the drug resistance of CRPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…28 Overexpression of carnitine palmitoyltransferase 1B (CPT1B), a rate-limiting step of fatty acid oxidation, is reported to significantly increase enzalutamide resistance via increasing AKT expression and phosphorylation in CRPC cells. 28 This indicates that enhanced fatty acid oxidation could promote the drug resistance of CRPC cells. Our study has found bicalutamide resistance induced SQLE highly expression refer to increased mitochondrial OXPHOS, which supplied energy source to maintain proliferation and metastasis in CPRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, targeting CPT1B in cancers with abnormal lipid metabolism and fatty acid oxidation (castration-resistant prostate cancer) is proposed. CPT1B overexpression is correlated with poor prognosis in prostate cancer (Abudurexiti et al, 2020). However, the role of CPT1B in CC is yet to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Carnitine palmitoyltransferase 1B (CPT1B) has been reported to be related with tumor proliferation and metastasis through regulating EMT in BLCA [34]. Overexpression of CPT1B was correlated with worse OS in prostate cancer [35]. Further study has revealed that AR-mediated CPT1B promoted castration-sensitive and castration-resistant prostate cancer (CRPC) progression by upregulating AKT expression and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%